The Modulating Force of Organizational Culture: Innovating, Aligning, and Skill-Building for Enhanced Business Performance - Dr. Dzingai Katsamba (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: The study aims to demonstrate that transformational leadership enhances the business performance of SMEs, mediating role demonstrating how innovation, culture, skills, and competencies influence business performance, as well as the moderating effect of organizational culture. Methodology: Drawing on dynamic capability theory, a quantitative, cross-sectional research design was used to collect data from employees of SMEs (N=). Data were analyzed using SmartPLS 3.0.Findings: The results show that transformational leadership has a direct positive and significant impact on innovation (Beta=0.644, p=0.000), culture (Beta=0.476, p=0.000), and skills & competencies (Beta=0.438, p=0.000). Also, Innovation (Beta = -0.104, p= 0.001), culture (Beta = 0.084, p = 0.000), and skills & competencies (Beta = 0.122, p = 0.000) have a mediating, negative, and significant impact on the relationship between transformational leadership and business performance. Organizational culture has moderating impact on innovation (Beta=-0.259, p=0.000), culture (Beta=0.092, p=0.000), skills & competencies (Beta=-0.141, p=0.000) and business performance. The findings highlight that, in striving for success with organizational factors, African SMEs must engage in cultural stewardship to create an adaptive environment, meaningfully leveraged by vision-led leadership and human capital, to provide clarity through evidence-informed direction for policymakers and managers seeking organizational performance. Implications/Novel Contribution: This study is a useful resource for decision-makers seeking to facilitate the growth and developmental trajectory of their firms to meet future challenges.